Sertraline-Associated Urinary Incontinence in an Adolescent With Obsessive-Compulsive Disorder - Nacharin Phiphopthatsanee; Atiporn Therdyothin (Journal of Clinical Psychopharmacology, 2024)
Phiphopthatsanee, Nacharin MD, MRCPsych; Therdyothin, Atiporn MD, MRes Author Information
Keywords: Obsessive-Compulsive Spectrum Disorders; Botulinum Toxin and Related Neurological Disorders; Electroconvulsive Therapy Studies